2016
DOI: 10.1039/c6cp02931k
|View full text |Cite
|
Sign up to set email alerts
|

The cluster-assembled nanowires based on M12N12 (M = Al and Ga) clusters as potential gas sensors for CO, NO, and NO2 detection

Abstract: The advances in cluster-assembled materials where clusters serve as building blocks have opened new opportunities to develop ever more sensitive gas sensors. Here, using density functional theory calculations, the structural and electronic properties of cluster-assembled nanowires based on M12N12 (M = Al and Ga) clusters and their application as gas sensors have been investigated. Our results show that the nanowires can be produced via the coalescence of stable M12N12 fullerene-like clusters. The M12N12-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 53 publications
(71 reference statements)
4
33
0
Order By: Relevance
“…34 The accuracy of the GGA-PBE and DNP combination to be used in investigations of the structural and electronic properties of (gases adsorption on) GaN systems has been demonstrated. 16,17,[35][36][37] 3. Results and discussion…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…34 The accuracy of the GGA-PBE and DNP combination to be used in investigations of the structural and electronic properties of (gases adsorption on) GaN systems has been demonstrated. 16,17,[35][36][37] 3. Results and discussion…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, the adsorption of O 2 molecule on the PL-GaN sheet is endothermic, indicating that the PL-GaN sheet is very inert to oxidation, similar to that of O 2 adsorption on GaN nanowires. 17 The adsorption of H 2 molecule on the PL-GaN surface is very different from the adsorption of hydrogen at the GaN surface. 48,49 Krukowski group 48,49 has found that for relatively low hydrogen coverage, the H 2 molecule adsorbs dissociatively, leading to disintegrating into separate H atoms at GaN (0001) surface.…”
Section: -47mentioning
confidence: 99%
See 2 more Smart Citations
“…[30][31][32] Even though GaN nanowire-based devices, including tunnel-injected DUV light-emitting diodes (LEDs) 33 and LEDs for monolithic metal-optoelectronics 34 and high-power light emitters, 35 have recently been realized, understanding and optimizing the electrothermal characteristics 36,37 of GaN-based nanowires is critical for identifying and achieving their full potential in opto-electrothermal device applications. 38,39 As a consequence of the thermal activation of non-radiative recombination channels, we observed an increasing trend in the amount of generated photoinduced entropy of the InGaN nanowire system as its temperature approached room temperature, which is a valid assessment of the thermodynamic disorder in photoluminescent semiconducting materials. 40 Furthermore, the non-radiative photocarrier recombination lifetimes in nanostructured materials are naturally shorter than those of bulk structures owing to their higher surface-to-volume ratios.…”
Section: Introductionmentioning
confidence: 85%